Pengaruh Governance terhadap Firm Value dengan Institutional Ownership sebagai Variabel Moderasi pada Perusahaan Cyclicals dan Non-Cyclicals di BEI 2021-2023 - Elda Furi Lestari; Ambar Kusumaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The study investigates the impression of governance on firm value, along with the moderating contribution of institutional ownership, among companies operating in the consumer cyclicals and consumer non-cyclicals scope registry on the Indonesia Stock Exchange (IDX) over the 2021-2023 term. Drawing on a specimen of 42 companies and 126 observations, a quantitative panel data methodology was adopted, by data gathered through purposive sampling. The Bloomberg Governance Score was used to measure governance, Tobin's Q served as a representative for firm value, institutional ownership was the tempering variable, and firm size, leverage, and profitability were involved as control variables. Model appointment was executed adopting the Chow and Hausman Tests in EViews 14, revealing that the Random Effects Model (REM) outperformed suitable estimation approach. The results reveal that governance has a negligible affect on firm value. Moreover, institutional ownership is incapable of intensiying the link between governance and firm value. Based on these outcomes, ESG-based governance signals remain unexplored optimally absorbed by investors in the Indonesian capital market; hence, reinforcing governance reporting standards and enhancing investor ESG literacy are considered essential steps toward integrating non-financial information into investment decision-making.